Altered Levels and Isoforms of Tau and Nuclear Membrane Invaginations in Huntington’s Disease - Fernández-Nogales, Marta; Lucas, José J. (Frontiers in Cellular Neuroscience, 2020)
Since the early reports of neurofibrillary tau pathology in brains of some HD patients, mounting evidence of multiple alterations of tau in HD brain tissue has emerged in recent years. Such tau alterations range from increased total levels, imbalance of alternative splicing-generated isoforms (increased 4R-/3R-Tau ratio), hyperphosphorylation, and truncation. Besides, the detection in HD brains of a new tau histopathological hallmark known as tau nuclear rods (TNRs) or tau-positive nuclear indentations (TNIs) led to propose HD as a secondary tauopathy. After their discovery in HD brains, TNIs have also been reported in hippocampal neurons of early Braak stage AD cases and in frontal and temporal cortical neurons of FTD-MAPT cases due to the MAPT intronic IVS10+16 mutation which results in an increased 4R-/3R-Tau ratio similar to that observed in HD. TNIs are likely pathogenic for contributing to the disturbed nucleocytoplasmic transport observed in HD. A key question is whether correction of any of the mentioned tau alterations might have positive therapeutic implications for HD. The beneficial effect of decreasing tau expression in HD mouse models clearly implicates tau in HD pathogenesis. This beneficial effect might be exerted by diminishing the excess total levels of Tau or specifically by diminishing the excess 4R-tau, as well as any of their downstream effects. In any case, since gene silencing drugs are under development to attenuate both HTT expression for HD and MAPT expression for FTD-MAPT, it is conceivable that the combined therapy in HD patients might be more effective that HTT silencing alone.